(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article talked about antonyms as stylistic means often used in texts of fiction, about their originality in a word usage. Such properties of antonyms attract the special attention during work with text. Antonyms have influence on maintenance of text, especially at using of them as pair words in suggestion: they serve as his decoration, complement maintenance of characterizing. As a result of their able use an idea can be expressed more openly, distinctly. The use of antonyms in maintenance of text assists strengthening of expression, to the readers valuably sense of vivid description can the same be carried in work, foremost it touches contrasting descriptions. As a report new information giving a semantic colour artistic text is given. At the use of opposite concepts there is a process of generalization of philosophical idea in text, reader with the impressions comes to the reflections.